Impact of enhanced chest CT with three-dimensional reconstruction combined with preoperative olive oil administration on the incidence of postoperative chylothorax: a retrospective study - Xindong Luo; Di Lu; Ziqiang Wang; Jingyi Wang; Ruozhu Dong; Yaping Wang; Wei Cao; Dacheng Jin; Zhaohao Lin; Haochi Li; Pengcheng Du; Yunjiu Gou; et al. (Journal of Cardiothoracic Surgery)
Abstract Background Chylothorax is a rare but potentially life-threatening complication after esophageal cancer resection. This study aims to investigate the impact of a strategy combining preoperative three-dimensional (3D) reconstruction of contrast-enhanced chest CT with olive oil ingestion on the incidence of chylothorax following esophageal cancer resection. Methods We retrospectively analyzed the clinical data of 357 patients who underwent esophageal cancer resection in the Department of Thoracic Surgery at Gansu Provincial People’s Hospital from January 2019 to June 2024. Among them, 179 patients who underwent preoperative 3D reconstruction of contrast-enhanced chest CT combined with oral olive oil administration were assigned to the 3D reconstruction group, while 158 patients who did not receive these interventions served as the control group. The primary outcome measures included the incidence of chylous leakage and related perioperative outcomes. Results All patients in both groups underwent surgeries successfully without any perioperative deaths. Compared to the control group, the 3D reconstruction group exhibited a significant decrease in the incidence of postoperative chylothorax (0% versus 8.2%, P < 0.001). The visualization rate of the thoracic duct during surgery was higher in the 3D reconstruction group compared to the control group (93.85% vs. 48.73%). Furthermore, patients in the 3D reconstruction group had less intraoperative bleeding (P = 0.003), shorter postoperative hospital stays (P = 0.003), and reduced chest drainage in the first three postoperative days (P < 0.001). Conclusion This study reveals that preoperative three-dimensional reconstruction of chest using enhanced CT allows for the anticipation of thoracic duct anatomy. Additionally, the combination of preoperative oral olive oil administration significantly enhances the intraoperative visualization of the thoracic duct. This integrated strategy effectively reduces the incidence of postoperative chylothorax, demonstrating promising clinical application prospects.